DEFINING INNOVATION WITH RESPECT TO NEW MEDICINES: A SYSTEMATIC REVIEW FROM A PAYER PERSPECTIVE. (10th July 2018) - de Solà-Morales, Oriol; Cunningham, David; Flume, Mathias; Overton, Paul M.; Shalet, Natalie; Capri, Stefano
Abstract : Objectives: The aim of this study was to investigate how innovation is defined with respect to new medicines. Methods: MEDLINE, Embase, and EconLit databases were searched for articles published between January 1, 2010 and May 25, 2016 that described a relevant definition of innovation. Identified definitions were analyzed by mapping the concepts described onto a set of ten dimensions of innovation. Results: In total, thirty-six articles were included, and described a total of twenty-five different definitions of innovation. The most commonly occurring dimension was therapeutic benefit, with novelty and the availability of existing treatments the second and third most common dimensions. Overall, there was little agreement in the published literature on what characteristics of new medicines constitute rewardable innovation. Conclusions: Alignment across countries and among regulators, health technology assessment bodies and payers would help manufacturers define research policies that can drive innovation, but may be challenging, as judgements about what aspects of innovation should be rewarded vary among stakeholders, and depend on political and societal factors.